International Family Migration and the Dual-Earner Model - Martin Munk; Till Nikolka; Panu Poutvaara (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2017)
Gender differences in labor force participation are exceptionally small in Nordic countries. We investigate how couples emigrating from Denmark self-select and sort into different destinations and whether couples pursue the dual-earner model, in which both partners work, when abroad. Female labor force participation is slightly lower among couples that later emigrate, and drops considerably after migration outside the Nordic countries. Pre migration differences between couples subsequently migrating to different destinations are small. Our survey reveals that couple migration is usually driven by the male's job opportunities. The results suggest that increasing international migration may reduce women's career investments.
Keywords: D13; J12; J13; J16; F22; 330; Household production; Female labor force participation; Child care; International migration; Family migration